Association between androgenetic alopecia and psychological well-being: a systematic review and meta-analysis - Kong, Yuan; Shang, Yutong; Zhang, Liuwei (Frontiers in Psychiatry, 2025)
BackgroundAndrogenetic alopecia (AGA) is a prevalent chronic condition with health burden, yet its association with psychological well-being remains inconsistent. This study systematically examines differences in psychological well-being between AGA patients and non-AGA controls, focusing on symptoms of anxiety, symptoms of depression, stress, and other psychological issues.MethodsFollowing the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines, a systematic search was conducted across 7 databases (CNKI, Wanfang, PubMed, Web of Science, Cochrane, EMBASE, EBSCO series) from their inception to June 30, 2025. A total of 13 studies were included, comprising 2,737 AGA patients and 17,382 controls. Study quality was assessed using the Agency for Healthcare Research and Quality (AHRQ) tool for cross-sectional studies and Newcastle-Ottawa Scale (NOS) for case-control studies. Effect sizes were pooled using a random-effects model, supplemented by sensitivity analysis and publication bias assessment to ensure the robustness of the results.ResultsCompared to non-AGA controls, AGA patients demonstrated significantly higher levels of generalized anxiety symptoms (pooled SMD = -0.50, 95% CI [-0.99, 0.00], p = 0.05), social anxiety symptoms (pooled SMD = -0.50, 95% CI [-0.84,-0.16], p = 0.004), depression symptoms (pooled SMD = -0.38, 95% CI [-0.65,-0.12], p = 0.004), and perceived stress (pooled SMD = -1.09, 95% CI [-1.43,-0.74], p < 0.001). However, no significant difference was observed in general distress (pooled SMD = -0.01, 95% CI [-0.39,0.37], p = 0.97). Qualitatively, AGA patients also exhibited reduced self-esteem, life satisfaction, and emotional intelligence dimensions, along with greater body image dissatisfaction, somatization, interpersonal sensitivity, and psychoticism.ConclusionAGA patients experience increased levels of symptoms of anxiety, symptoms of depression, stress, body image dissatisfaction, somatization, interpersonal sensitivity, and psychoticism, as well as decreased self-esteem, life satisfaction, emotional intelligence, self-actualization, problem-solving ability, optimism, and happiness. In the future, clinical treatment should focus on patient psychological well-being through assessments and timely interventions, and further research should be conducted to provide precise clinical guidance.Systematic Review Registration[https://www.crd.york.ac.uk/PROSPERO/], identifier [CRD420250655604].